Complementary molecular methods detect undeclared species in sausage products at retail markets in Canada. (February 2018) - Naaum, Amanda M.; Shehata, Hanan R.; Chen, Shu; Li, Jiping; Tabujara, Nicole; Awmack, David; Lutze-Wallace, Cyril; Hanner, Robert
Abstract: Accurate food labelling is of utmost importance for food safety and consumer choice in the food chain. Complete or partial substitution, whether intentional or unintentional, may introduce food pathogens or allergens to a product or affect personal or religious beliefs. Several studies around the world have reported different degrees of species substitution in meat products but no similar studies have been conducted in the Canadian market for sausage products. In this study, 100 raw meat sausage samples that were labelled as single meat species products (beef, pork, chicken or turkey) were collected from retail establishments across Canada and were surveyed for the presence of a panel of non-labeled species. The predominant meat species were determined using DNA barcoding and contaminant or unclaimed meat species were detected using digital droplet PCR using species specific primers and probes. All samples were also tested for presence of horse meat using real-time PCR. All samples contained the predominant species matching the label species except for five turkey sausage samples which contained chicken as the predominant species. Second, this analysis showed that 6% of beef sausages also contained pork, 20% of chicken sausages contained turkey while 5% contained beef, and 5% of pork sausages also contained beef. Five samples labeled as turkey sausage contained no turkey and one pork sample was found to contain horse meat. The overall mislabeling rate detected in this study was 20% and the results provide a baseline for assessing species mislabeling in processed meat products in Canada. Highlights: The predominant meat species were determined in sausage samples using DNA barcoding. Five turkey sausage samples contained chicken as the predominant species. Contaminant meat species were detected using digital droplet PCR. Undeclared species were detected in beef (6%), chicken (25%), and pork (5%) sausages. Real-time PCR assay revealed that one pork sample contained horse meat.